2018
DOI: 10.32448/entupdates.458981
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Perioperative I.V. Corticosteroids On Hearing Outcome Following Stapedotomy

Abstract: Objective: The purpose of this study is to investigate the effect of steroids on postoperative hearing outcome in patients with a clinical diagnosis of otosclerosis, who received intraoperative steroid treatment during surgery for conductive-type hearing loss. Methods: Between January 2014 and January 2017, 106 patients, comprising 43 men (40.6%) and 63 women (59.4%) between the ages of 18-64 (mean age: 44.1 ± 11.5 years), who had been diagnosed with otosclerosis resulting in conductive-type hearing loss, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We found a positive effect of perioperative corticosteroid therapy on stapes surgery hearing results. While this is in contrast with the findings of other clinical investigations [13,14] the beneficial inner ear effect of corticosteroids in ASNHL has been proven already [15], furthermore, multiple non-clinical studies have shown a protective effect in case of cochlear trauma and otologic procedures [9,10,16]. Methylprednisolone has a protective inner ear effect by reducing vestibular trauma and electrode impedances after cochlear implantation [17].…”
Section: Interpretation Of the Other Resultsmentioning
confidence: 80%
“…We found a positive effect of perioperative corticosteroid therapy on stapes surgery hearing results. While this is in contrast with the findings of other clinical investigations [13,14] the beneficial inner ear effect of corticosteroids in ASNHL has been proven already [15], furthermore, multiple non-clinical studies have shown a protective effect in case of cochlear trauma and otologic procedures [9,10,16]. Methylprednisolone has a protective inner ear effect by reducing vestibular trauma and electrode impedances after cochlear implantation [17].…”
Section: Interpretation Of the Other Resultsmentioning
confidence: 80%
“…Simalarly, Çelik et al found no statistically significant difference between patients who did receive intra-operative single-dose IV corticosteroid injections and patients who did not receive IV corticosteroid injections group in terms of preoperative and postoperative air-bone conduction levels. 29 Székely et al found the positive effect of corticosteroid treatment on postoperative hearing levels. 30 Despite the above encouraging results, our study has some limitations.…”
Section: Discussionmentioning
confidence: 98%